Frameless Nonstereotactic Image-Guided Surgery of Supratentorial Lesions: Introduction to a Safe and Inexpensive Technique - Callovini, Giorgio; Sherkat, Shahram; Callovini, Gemma; Gazzeri, Roberto (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Background We describe a simple, safe, and inexpensive technique that through the comparison of three-dimensional (3D)-rendered magnetic resonance (MR) images and real anatomy allows us to navigate and remove brain lesions, including those without cortical appearance, by direct recognition of anatomical landmarks. Preoperative planning no longer requires the use of fiducials and can therefore be performed out a stereotactic setting.Methods MR Digital Imaging and Communications in Medicine format scans of 93 patients were reconstructed using MRIcro freeware for their three-dimensional rendering (3DR). The main location of the lesions was rolandic or left temporal, and most of them were without cortical appearance (78%). The two-dimensional (2D) sets of images were processed by the software to perform a 3DR, thus obtaining a virtual model of the patient's head. Using the same 2D sets, the edges of the lesion's images were contoured by the region of interest (ROI) tool. In the next step, the ROI was projected onto the surface of the virtual model of the patient's head, thus helping to attain the best identification of the craniotomy area. MRIcro automatic segmentation function, the Brain Extraction Tool (BET), provides a clear 3DR of the cortical surface. We used BET to display gyri, sulci, and perilesional vessels to have further anatomical landmarks to guide the surgical approach.Results The lesions were accessed through an optimally suited craniotomy. The visual matching of the cortical surface with reconstructed 3D images of the cortex permitted a fast localization of cortical and subcortical lesions. The major limitation is the depth of a lesion deeper than 3 cm. In these cases, the use of frame-based or frameless techniques still seems safer and more advantageous.Conclusions The shape recognition of the cortical landmarks was not biased by brain distortion because the sulci and cortical vessels almost always had a relationship to each other that was not modified by edema or cerebrospinal fluid leakage. This 3DR allows us to reconstruct a virtual anatomy in an easy, portable, and inexpensive way. In selected cases, this technique represents a valid and safe alternative to the use of costly neuronavigation tools and is potentially helpful in developing countries.
Keywords: image-guided surgery; MRIcro; cortical sulci; neuronavigation; stereotaxy